Driving Sustainability Performance in Indonesian SMEs: The Role of Cloud-Based Accounting Information Systems and Digital Transformation - Purwantini Anissa Hakim; Prasetya Wahyu Anggit; Hidayati Luk Luk Atul; Maharani Betari; Aligarh Frank (E3S Web of Conferences)
This study aims to investigate the impact of using a Cloud-Based Accounting Information System (CB-AIS) on digital transformation and its subsequent effect on the sustainability performance of Small and Medium Enterprises (SMEs) in the food and beverage sector in Indonesia. Sustainability performance is measured across three dimensions: economic, social, and environmental. Quantitative research methodology has been adopted, and the survey methodology has been conducted in this paper. Data were collected from 151 SMEs using the convenience sampling method. Structural Equation Modelling-Partial Least Squares (SEM-PLS) was employed for data analysis. The results reveal that CB-AIS has a significant positive effect on digital transformation and sustainability performance. Digital transformation also significantly influences sustainability performance and serves as a partial mediator in the relationship between CB-AIS and sustainability performance. These findings underscore the critical role of CB-AIS implementation in facilitating the digital transformation of SMEs, ultimately enhancing their sustainability across economic, social, and environmental dimensions. This study provides theoretical and practical contributions to the development of digital strategies for SMEs in Indonesia’s food and beverage sector.